2016
DOI: 10.1108/ijwhm-11-2015-0068
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the relationship between psychosocial hazard and ambulatory physiological response in higher education employees

Abstract: Purpose As exposure to psychosocial hazard at work represents a substantial risk factor for employee health in many modern occupations, being able to accurately assess how employees cope with their working environment is crucial. The workplace is generally accepted as being a dynamic environment, therefore, consideration should be given to the interaction between employees and the acute environmental characteristics of their workplace. The purpose of this paper is to investigate the effects of both acute deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Overall, high job demands including role conflict, have previously been associated with negative effects on health-related outcomes among healthcare workers but also among workers in general (Sverke et al, 2017). Of these outcomes, most research have investigated different cardiovascular outcomes and shown that physiological changes may constitute an important mechanism linking various occupational demands to poor health (Campbell et al, 2016;Sverke et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, high job demands including role conflict, have previously been associated with negative effects on health-related outcomes among healthcare workers but also among workers in general (Sverke et al, 2017). Of these outcomes, most research have investigated different cardiovascular outcomes and shown that physiological changes may constitute an important mechanism linking various occupational demands to poor health (Campbell et al, 2016;Sverke et al, 2017).…”
Section: Discussionmentioning
confidence: 99%